PHP 7 : real world application development : use new features of PHP 7 to solve practical, real-world problems faced by PHP developers like yourself every day : a course in three modules.: real world application development : use new features of PHP 7 to solve practical, real-world problems faced by PHP developers like yourself every day : a course in three modules. ([2016]) - Bierer, Doug; Hussain, Altaf; Jones, Paul
No abstract available